2006
DOI: 10.1111/j.1574-695x.2006.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating potential of supplementation with probiotics: a dose–response study in healthy young adults

Abstract: Certain probiotic microorganisms have been found beneficial in the treatment of immune-related diseases and may also affect immune function in healthy people. Intervention studies of probiotics in healthy humans are urgently required. Here, the immunomodulating potential of Bifidobacterium animalis ssp. lactis (BB-12) and Lactobacillus paracasei ssp. paracasei (CRL-431) was studied in a double-blind placebo-controlled parallel dose-response trial (n=71) based on five randomly assigned groups of young healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 46 publications
(53 reference statements)
1
37
0
Order By: Relevance
“…169,171 In contrast, supplementation of volunteers with L. fermentum ECET5716 for 2 weeks before and 2 weeks after vaccination with an inactivated trivalent infl uenza vaccine increased serum IL-12 levels before vaccination, and enhanced vaccine-induced elevations in serum TNF-α. 172 It also induced signifi cantly higher levels of specifi c IgA, but not IgG or IgM, compared with the placebo group.…”
Section: Probiotic Supplementation In Healthy Volunteersmentioning
confidence: 97%
See 2 more Smart Citations
“…169,171 In contrast, supplementation of volunteers with L. fermentum ECET5716 for 2 weeks before and 2 weeks after vaccination with an inactivated trivalent infl uenza vaccine increased serum IL-12 levels before vaccination, and enhanced vaccine-induced elevations in serum TNF-α. 172 It also induced signifi cantly higher levels of specifi c IgA, but not IgG or IgM, compared with the placebo group.…”
Section: Probiotic Supplementation In Healthy Volunteersmentioning
confidence: 97%
“…paracasei CRL-431) did not enhance phagocytosis at any of the four doses tested. 169 The effect size is frequently small and of questionable clinical relevance, although subjects with low innate immune responses may benefi t signifi cantly. 160,161,166 Of note, even though several small studies indicated that L. casei Shirota supplementation could increase NK cell and phagocytic activity, one of the probiotic supplementation studies with the highest methodological quality did not.…”
Section: Probiotic Supplementation In Healthy Volunteersmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunomodulatory effects of probiotics have mostly been studied in certain disease conditions, such as allergies [2] and inflammatory diseases [3,4] , though the general, healthy population mostly consumes probiotics. The immunomodulatory effects of probiotics in healthy populations have not been fully established and only a few randomized, double blind, placebo-controlled studies have addressed this question [5][6][7][8][9] . Also, there are few studies where the effects of different…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the recovery of BB-12 and CRL-431 from fecal samples was determined. The effects on various immune parameters were also studied and are to be published elsewhere (Christensen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%